SAN LUIS POTOSIECTROSCOPIC OBSERVATIONS OF COMET BENNETT - MENDEZ, ME (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1970)
Spectroscopy of Comet Bennett (1969i) taken from 22 to 28 of March 1970 is presented.
BOL OBS TONAN TACUB
Keywords: SPECTROSCOPIC, OBSERVATIONS, COMET BENNETT; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS